2017
DOI: 10.1038/srep45651
|View full text |Cite
|
Sign up to set email alerts
|

Patterns in the skin microbiota differ in children and teenagers between rural and urban environments

Abstract: The composition of human microbiota is affected by a multitude of factors. Understanding the dynamics of our microbial communities is important for promoting human health because microbiota has a crucial role in the development of inflammatory diseases, such as allergies. We have studied the skin microbiota of both arms in 275 Finnish children of few months old to teenagers living in contrasting environments. We show that while age is a major factor affecting skin microbial composition, the living environment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
110
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(116 citation statements)
references
References 59 publications
4
110
0
2
Order By: Relevance
“…3 The skin microbiota is different in children living in urban or rural environments, reflecting different exposure to environmental microbiotas and varying lifestyle. 4 We hypothesized that the nature connection in daycares can influence child microbiota and consequently affect the maturation of immunoregulation. We describe our pilot study comparing the skin microbiota and allergic outcomes (sensitization and self-reported symptoms) in children attending different types of daycares, considering the degree of nature contact.…”
Section: Nature-oriented Daycare Diversifies Skin Microbiota In Childmentioning
confidence: 99%
See 1 more Smart Citation
“…3 The skin microbiota is different in children living in urban or rural environments, reflecting different exposure to environmental microbiotas and varying lifestyle. 4 We hypothesized that the nature connection in daycares can influence child microbiota and consequently affect the maturation of immunoregulation. We describe our pilot study comparing the skin microbiota and allergic outcomes (sensitization and self-reported symptoms) in children attending different types of daycares, considering the degree of nature contact.…”
Section: Nature-oriented Daycare Diversifies Skin Microbiota In Childmentioning
confidence: 99%
“…1,3 The first Brazilian Allergy Project (PROAL I) study was carried out in 2004 with the objective of documenting the sensitization rates to the major allergens in Brazilian allergic children. 4 This was the first study of its kind, which contributed to better understanding of regional differences and enabled comparison with other countries. During the past decade, the prevalence of asthma and allergic diseases in children and adolescents has increased.…”
Section: Increased Sensitization To Several Allergens Over a 12-yearmentioning
confidence: 99%
“…On the other hand, children living in urban settings tend to have higher rates of sensitization and allergies (Stemeseder et al 2017), they also have a less diverse skin and gut microbiota than those living in rural settings (Lehtimaki et al 2017; Mah et al 2008). Living conditions, such as farms, that allow early contact with diverse microbial agents from the natural environment are thought to help the developing immune system of children (Ege et al 2006; Rook and Brunet 2005; Rook et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Lax et al [62] reported that household microbiota was "identifiable by family" and that "humans sharing a home were more microbially similar than those not sharing a home." Lehtimäki et al [63] studied skin microbiota and found an age-dependent difference between rural and urban children. Given the pace of recent progress, we can anticipate the emergence of stronger evidence in the near future regarding the nature and extent to which microbiology of built environments interacts with the human microbiome [64][65][66].…”
Section: Built Environment and The Human Microbiomementioning
confidence: 99%